Studi Aplikasi Sistem Resi Gudang di Kecamatan Mandastana Kabupaten Barito Kuala - Hartoni Hartoni; Umi Salawati; Dolok Saribu (Universitas Lambung Mangkurat, 2014)
The study is purposed: (1) to describe the SRG application carried out by the committee; (2) to identify the problems faced by SRG manager: (3) to excavate the obstacles encountered by farmers in using the SRG; and (4) to calculate cost and revenue margin of rice farming of the farmer as SRG user Descriptive analysis was used to answer the purpose. Several stages should be passed to issue the warehouse receipt which is time consuming and highly bureaucratic. As a result, only small rice farmers use the facility. Furthermore, the time to store the yield in the warehouse is not fit to the farmers need. Based on cost margin, the highest cost margin is spent by farmer from Desa Anjir Seberang Pasar I while Desa Tebing Rimbah, Berangas Timur, and Desa Lok Rawa are the lower. On contrary, the highest revenue margin are received by farmers from Desa Tebing Rimbah, Desa Berangas Timur, and Desa Lok Rawa; while farmers in Desa Anjir Serapat Pasar l received smaflest revenue margin.